(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2024)
The aim of present study was to investigate the preliminary phytochemical, physicochemical, TLC, minerals analysis and In-vitro antioxidant activity of leaves of ethanolic extract of Heldigardia populifolia. The preliminary phytochemical screening of ethanolic extract showed the presence of triterpenoids, flavonoids, glycosides, sterols, steroids, phenols, carbohydrates and saponins. The composition of minerals found in the leaf powder was within the permissible limits. TLC analysis of ethanol extract showed the five spots which indicate the presence of five phytoconstituents. The extractive value of ethanol was high than acetone. Ash values were within the limits. The in-vitro antioxidant activity of ethanolic extract increased with increasing the concentration. The ethanolic extract in all the concentration showed the significant antioxidant activity.